Mental Health Overview in Bullying Victim Students: A Descriptive Analysis - Yusuf Hanafi Lubis; Ivena Hotmarina Septiani Nainggolan; Linda Mutiara Harahap; Risna Risna; Sashi Pangestuty (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To identify the impact of bullying behavior on the mental health of students who are victims of bullying.Methods: This was a cross-sectional descriptive quantitative study on 105 students in Medan Perjuangan district from November - December 2021. Sampling was performed using accidental sampling techniques on students living in the study area. A questionnaire was used to collect data and analysis was performed using univariate analysis with an estimated value of 95% confidence of 5%. Results: More than 70% of respondents received some forms of bullying such as body shaming, intelligence discrimination, and parental work shaming, discrimination based on their religion and beliefs, and abusive words. More than 60% of students were also discriminated, ridicule, and subjected to physical violence. About 50% of respondents were also bullied based on their financial, racial/ethnicity, and skin color traits and received physical abused.Conclusion: There is a link between mental health conditions and bullying behavior in students who are victims of bullying.